KEJADIAN OTITIS EKSTERNA PADA MASYARAKAT PENEBEL TABANAN DAN YANGAPI BANGLI YANG BERKUNJUNG KE BAKTI SOSIAL STAF MEDIS FUNGSIONAL TELINGA HIDUNG TENGGOROKAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - RUMAH SAKIT UMUM PUSAT SANGLAH PADA TAHUN 2012 - Putu Teguh Aryanugraha; Eka Putra Setiawan (Intisari Sains Medis, 2016)
Indonesia is a tropical country which in some places have there own temperature and humidity criteria factors predisposing to otitis externa is usually triggered by the growth of fungi that are responsible for the onset of otitis externa. The research was conducted in two places, namely in the village of Penebel Tabanan and the village of Yangapi Bangli. The aim to determine the prevalence of otitis externa, especially in people who follow social events in the village Penebel and Yangapi. This research was carried out by quantitative descriptive design with a population that is affordable and Yangapi Penebel villagers who come to charity ENT Division Sanglah Hospital. The incidence of OE in the village Penebel was 6 of 66 patients and in the village Yangapi was 3 of 96 patients. Variants OE in the village of the same Penebel lot of male patients men and women with a lifespan of 41 years and above, whereas the incidence in the village OE Yangapi more on men with an age range 21-30 years. At this research showed otitis externa patients who come to social event in both villages were 9 people from 162 patients who came to the social event ENT Division Sanglah Hospital.